Study of the process of grain pre-threshing by working bodies of a combine harvester header - Sheychenko, Victor; Dudnikov, Igor; Kuzmych, Alvian; Shevchuk, Misha; Shevchuk, Vitaliy; Pushka, Alexander; Hruban, Vasyl; Tolstushko, Mykola; Tolstushko, Nataliya (Eastern-European Journal of Enterprise Technologies, 2017)
We improved the combined technological process of transportation and threshing of GSM and developed the device of preliminary grain threshing for a grain header of KZS 9-1 «Stavutich» harvester, which made it possible to separate 30–35 % of grain at the early phases of its transportation to TSS of a combine. We established that the coefficient of separation of grain from cones in a header with an intermediate thrashing drum, which contains four additional tooth-shaped bars of 30 mm in height, has the highest (0.32) value. We developed a calculation and experimental method for determining the amount (degree) of grain separation by a device of a header of a combine harvester. The method is based on the results of simulation of the combined process of transportation and threshing of grain caused by the interaction of a drum with grain and straw mass. We analyzed and proved the complex influence of structural parameters of the device and modes of implementation of the combined process of transportation and threshing of GSM at the level of separation of grain. And this make it possible to establish a theoretical dependence of the grain separation coefficient. The noted theoretical dependence provides the possibility to substantiate rational parameters and operating modes of the device of preliminary grain threshing of a combine harvester analytically. We determined dependences of the grain separation coefficient on the speed of a combine experimentally. The dependences take into account cancellations of mechanized technological operations caused by changes in kinematic operating modes of a combine, a number of stops and their height on a drum of a device of preliminary grain threshing